Perancangan UI/UX Aplikasi Kasir Toko Rieska Dengan Metode Design Thinking - Faturrahman Ardiansyah; Apriansyah Apriansyah (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This research aims to develop a cashier application to improve efficiency and user experience in Rieska stores. By using the UI/UX design method, this application is designed to facilitate transactions and inventory management. The design results show a cashier application that is responsive and easy to learn. Users provided positive feedback, indicating wider adoption in the retail environment. This research highlights the importance of developing cashier applications that focus on user needs in improving efficiency and user experience in retail businesses.